Power splitting strategy for solar hydrogen generation. (10th April 2015) - Dou, Xin Xu; Simic, Milan; Andrews, John; Mo, John P.T.
A standalone solar–hydrogen power generation system employing photovoltaic array and hydrogen storage of excess energy is an attractive solution for remote and portable applications. A demonstration system has been designed and built focus on an integrated load split and maximum power point tracker to meet the load and divert surplus power to produce hydrogen for storage. Key functional requirements of a control system are defined. The dynamics of PEM electrolyser is studied through experimental testing, and its response time is presented and analysed. A demonstration system designed to perform load splitting and maximum power point tracking is proposed and its performance is evaluated experimentally. The positive results lead to constructing a control system control and self–adjust voltage output which accomplish load splitting and maximum power point tracking automatically.